2015
DOI: 10.1088/1748-6041/10/4/045024
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of the modulatory effects of antibacterial silver doped calcium phosphate-based ceramic nano-powder on proliferation, survival, and angiogenic capacity of different mammalian cells in vitro

Abstract: In this study, the antibacterial, cytotoxic, and angiogenic activities of silver doped calcium phosphate-based inorganic powder (ABT or PAG) were systematically investigated. ABT powders containing varying silver content were fabricated using a wet chemical manufacturing method. Antibacterial efficiencies of the ABT powders were investigated using a standard test with indicator bacteria and yeast. The cytotoxic effects of ABT on three different fibroblast cells and human umbilical vein endothelial cells (HUVEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…However, in vitro responses can be cell type specific as high concentrations of labile Ag‐containing surface coatings are known to be toxic to human fetal osteoblasts . We also found that both attachment and growth of HDMEC is well tolerated on Ag‐coated surfaces, similar to that described for human umbilical vein endothelial cells grown on silver‐doped ceramic nanopowder . In a mouse model where higher concentrations of Ag‐nanoparticles are released into the microcirculation, significant toxicity on endothelium has also been reported .…”
Section: Discussionsupporting
confidence: 87%
“…However, in vitro responses can be cell type specific as high concentrations of labile Ag‐containing surface coatings are known to be toxic to human fetal osteoblasts . We also found that both attachment and growth of HDMEC is well tolerated on Ag‐coated surfaces, similar to that described for human umbilical vein endothelial cells grown on silver‐doped ceramic nanopowder . In a mouse model where higher concentrations of Ag‐nanoparticles are released into the microcirculation, significant toxicity on endothelium has also been reported .…”
Section: Discussionsupporting
confidence: 87%
“…Both pure and silver ion doped calcium phosphate‐based micro and macro porous ceramic beads were fabricated using wet chemically synthesized calcium phosphate powders. Synthesis procedure of the silver ion doped calcium phosphates and the results of the silver release and toxicity studies has been reported in the previous studies 19,20,27,28 . In general, silver nitrate was dispersed and mixed with calcium hydroxide in pure water.…”
Section: Methodsmentioning
confidence: 99%
“…Our group has previously reported the development of a new silver ion doped nano‐size calcium phosphate‐based ceramic powder 19,20,27 . It was demonstrated that the coating prevented infection and did not disturb angiogenesis which plays a key role in osseous tissue growth, and at used concentration it was not cytotoxic 28 . After successful use of this material as a coating to prevent implant‐associated infections, it was thought that it would also be effective in the treatment of bone infection as a bone graft substitute.…”
Section: Introductionmentioning
confidence: 99%
“…This may be caused by the fact that in the agar diffusion test of chitosan, the agar did not diffuse through the medium, so that only the organism in direct contact with the active site of chitosan was inhibited. 1,13,15,18 Another reason can be that S. aureus and E. coli bacteria that were used may have gained resistance to chitosan. Bacteria can increase their resilience over time to survive.…”
Section: In Vitro Antibacterial Activitymentioning
confidence: 99%